A Recombinant System and Reporter Viruses for Papiine Alphaherpesvirus 2 - Abdul Rahman Siregar; Sabine Gärtner; Jasper Götting; Philipp Stegen; Artur Kaul; Thomas F. Schulz; Stefan Pöhlmann; Michael Winkler (Viruses, 2022)
Primate simplex viruses, including Herpes simplex viruses 1 and 2, form a group of closely related herpesviruses, which establish latent infections in neurons of their respective host species. While neuropathogenic infections in their natural hosts are rare, zoonotic transmission of Macacine alphaherpesvirus 1 (McHV1) from macaques to humans is associated with severe disease. Human infections with baboon-derived Papiine alphaherpesvirus 2 (PaHV2) have not been reported, although PaHV2 and McHV1 share several biological properties, including neuropathogenicity in mice. The reasons for potential differences in PaHV2 and McHV1 pathogenicity are presently not understood, and answering these questions will require mutagenic analysis. Here, we report the development of a recombinant system, which allows rescue of recombinant PaHV2. In addition, we used recombineering to generate viruses carrying reporter genes (Gaussia luciferase or enhanced green fluorescent protein), which replicate with similar efficiency as wild-type PaHV2. We demonstrate that these viruses can be used to analyze susceptibility of cells to infection and inhibition of infection by neutralizing antibodies and antiviral compounds. In summary, we created a recombinant system for PaHV2, which in the future will be invaluable for molecular analyses of neuropathogenicity of PaHV2.